Hypertrophic Cardiomyopathy: From Phenotype and Pathogenesis to Treatment - Cheng, Zeyi; Fang, Tingting; Huang, Jinglei; Guo, Yingqiang; Alam, Mahboob; Qian, Hong (Frontiers in Cardiovascular Medicine, 2021)
Hypertrophic cardiomyopathy (HCM) is a common inherited cardiovascular disease presents in 1 of 500 of the general population. It’s caused by more than 1400 mutation in 11 or more genes encoding proteins of the cardiac sarcomere. HCM presents a heterogeneous clinical profile and complex pathophysiology, and the most frequent cause of sudden cardiac death (SCD) in young people, also can cause functional disability from heart failure and stroke (caused by atrial fibrillation). Moreover, current treatments for HCM including medication, surgery, which can only slow down the progression and relieve symptoms, including implanted cardiac defibrillator (ICD) to prevent SCD. Lack of effective treatments for this disease. But, HCM is entering a phase of intense translational research that holds promise for major advances in disease-specific therapy. Main insights into the genetic landscape of HCM have enhanced our understanding of the molecular pathogenesis, and offered potential targets for the development of therapeutic agents. In the near future, the field of HCM treatment will rapidly expand, based on ongoing efforts. We review critical discoveries about the development of HCM’s treatments, and their implications for future research, are discussed.